(untitled) (Journal of the College of Basic Education, 2023)
This study was carried out to evaluate the effect of two fungi, Trichoderma viride and Trichoderma harzianum, and two isolates of Glomus mosseae (G1) and (G2), and the interaction between them on the emergence of seedlings and the growth of tomato plants, Lycopersicon esculentum Mill. The results showed that all treatments caused a significant reduction in the time required for seedling emergence compared to the comparison treatment, and the two treatments T. harzianum+G1, T. harzianum+G2 in reducing the period required for the plant and increasing the percentage of seedling emergence compared to the rest of the treatments, which were significantly superior to the control treatment.The results also showed that all treatments caused a significant increase in most of the studied plant growth parameters compared to the control treatment, which included the size of the rootstock, plant height, fresh weight of the shoot, fresh weight of the rootstock, dry weight of the shoot, dry weight of the rootstock, number of leaves, Number of flowers, leaf area and total chlorophyll concentration in plant leaves with the superiority of the two treatments T. harzianum+G1 and T. harzianum+G1. harzianum+G2, as they recorded (3.33, 3.7) ml, (31.66, 27) cm, (9.08, 9.74) gm, (2.33, 3.22) gm, (1.08, 2.19) gm, (0.18, 0.23) gm, (33.66, 38) Leaves (2, 4.66) flowers, (30.85, 41.36) cm2, (20.5, 25.65) mg total chlorophyll / g dry tissue, respectively, compared to the comparison treatment, which recorded (1.1) ml, (11.33) cm, (1.44) cm. g, (0.41) g, (0.14) g, (0.02) g, (7.33) leaf, (0) flower, (10.86) cm2 / plant and (9.03) mg total chlorophyll/g dry tissue, respectively.